Production of Bovine Colostrum for Human Consumption to Improve Health - Kaplan, Merve; Arslan, Ayşenur; Duman, Hatice; Karyelioğlu, Melda; Baydemir, Barış; Günar, Bilgetekin Burak; Alkan, Merve; Bayraktar, Ayşe; Tosun, Halil İbrahim; Ertürk, Melih; Eskici, Günay; Duar, Rebbeca M.; et al. (Frontiers in Pharmacology, 2022)
Colostrum contains all essential nutrients for the neonate during the first days of life, with impacts that continue far beyond these first days. Bovine colostrum has been used for human consumption due to the high concentrations of bioactive proteins, vitamins, minerals, growth factors, as well as free and conjugated oligosaccharides. Processes involved in the preparation of bovine colostrum for human consumption play a pivotal role in preserving and maintaining the activity of the bioactive molecules. As bovine colostrum is a multifunctional food that offers a myriad of benefits for human health, assessing the main processes used in preparing it with both advantages and disadvantages is a crucial point to discuss. We discuss major processes effects for colostrum production on the nutritional value, some advanced technologies to preserve processed bovine colostrum and the end-product forms consumed by humans whether as dairy products or dietary supplements.